Peningkatan Motivasi Berwirausaha dan Mutu Usaha Mikro Melalui Pelatihan Manajemen SDM - Krisnatalia, Heni; Hendrajaya, Hendrajaya (Journal of Dedicators Community, 2025)
Community Service Activities aim to provide SMEs with capabilities. The Community Service Program aims to ensure that SMEs have an entrepreneurial spirit so that there is business continuity which can ultimately increase income. The targets of this community service activity are MSME business actors in Nongkosawit Village, Gunungpati District, Semarang City. Mentoring methods include questions and answers, discussions and lectures. Mentoring activities are carried out as follows: (1) building entrepreneurial spirit, (2) improving production skills. The output of this activity is: 1) The entrepreneurial spirit of MSMEs is increasingly encouraged. 2) MSMEs are able to develop skills with a variety of creativity and be more sustainable by providing insight into product packaging, branding and attractive taglines for their business.